Polymorphic transitions during nonclassical nucleation and growth in the colloidal heteroepitaxy - Jun Nozawa; Masahide Sato; Satoshi Uda; Kozo Fujiwara (Communications Physics)
Abstract The control of polymorphs is crucial for material synthesis, requiring molecular-level understanding of crystallization mechanisms. However, the mechanisms governing polymorph selection during crystallization remain incompletely understood. Here, we demonstrate the realization of polymorphs in single-component colloidal crystals as epitaxial phases through heteroepitaxial growth. We observed three types of PTs that led to nonclassical behavior in nucleation, growth, and dissolution. The probability of these PTs during nucleation depended on the stability of the metastable cluster rather than that of the phase. Furthermore, the size of the polymorph is a critical parameter for PTs during growth. These PTs determined nucleation and growth pathways, ultimately influencing the product. Additionally, we demonstrate polymorphic control by adding differently sized particles, exploiting their effects on cluster formation due to differences in the structure of polymorphs. Our findings provide insights into the molecular mechanisms of PTs and their impact on crystallization pathways, offering a strategy for control.